Evaluating the Safety and Efficacy of Asundexian in Cardiovascular Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zainab Arif MBBS; Muhammad Ashbar Wadood MBBS; Sania Malahat MBBS; Mehmood Ahmad MBBS; Maliha Khalid MBBS; Saman Adnan MBBS; Erum Siddiqui MBBS; Aminath Waafira MBBS (Clinical and Applied Thrombosis/Hemostasis, 2025)
Background Thromboembolic events remain a major cause of morbidity and mortality in cardiovascular diseases, particularly myocardial infarction, atrial fibrillation (AF), and ischemic stroke. While standard anticoagulants reduce these events, their use is limited by bleeding risks. Asundexian, a Factor XIa inhibitor, has emerged as a potential agent to prevent thrombosis while preserving hemostasis. This meta-analysis evaluates its safety and efficacy across cardiovascular conditions. Methods Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic review and meta-analysis was registered with PROSPERO (CRD420251039715). Randomized controlled trials (RCTs) comparing Asundexian with placebo or active controls were identified via PubMed, Scopus, and CENTRAL. Outcomes included all-cause mortality, cardiovascular death, ischemic stroke, stroke or systemic embolism, major/clinically relevant non-major bleeding, and adverse effects. Data were analyzed using a random-effects model; study quality was assessed via Cochrane Risk of Bias Tool 2.0. Results Four RCTs were included. The pooled analysis showed no significant difference in all-cause mortality between Asundexian and control (RR 1.04, 95% CI 0.73-1.48, P  = .83), with low heterogeneity (I² = 13%). Ischemic stroke rates were also similar (RR 1.64, 95% CI 0.51-5.25, P  = .40), but with high heterogeneity (I² = 89%). Cardiovascular-related mortality did not differ between groups (RR 1.13, 95% CI 0.77-1.66, P  = .53; I² = 0%). For safety outcomes, ISTH major or clinically relevant non-major bleeding showed a non-significant trend toward lower risk with Asundexian (RR 0.63, 95% CI 0.21-1.91, P  = .41; I² = 77%). Stroke or systemic embolism (RR 1.29, 95% CI 0.08-20.70, P  = .88) and adverse events (RR 1.00, 95% CI 0.95-1.04, P  = .85) were comparable between groups. Conclusion Asundexian demonstrated no significant difference compared to control in all-cause mortality, ischemic stroke, or cardiovascular-related mortality. While there was a non-significant trend toward reduced bleeding risk, no clear benefit was observed for stroke prevention or systemic embolism. The safety profile was comparable, with no increase in adverse events. These findings suggest that Asundexian, at the studied doses, does not provide significant clinical advantages in mortality or thromboembolic outcomes but may have a favorable bleeding profile. Further research is needed to define its potential role in specific high-risk populations.